Human factors in land use planning and urban design. Methods, practical guidance, and applications. - Stevens, Nicholas J.; Salmon, Paul M.; Walker, Guy H.; Stanton, Neville (CRC Press, 2018)
The integration of Human Factors in Land Use Planning and Urban Design (LUP & UD) is an exciting and emerging interdisciplinary field. This book offers practical guidance on a range of Human Factors methods that can be used to rigorously and reliably explore LUP & UD. It provides new ways to interpret urban space and detail context sensitive analysis for the interpretation and design of our surroundings. The methodologies outlined allow for the consideration of the technical aspects of the built environment with the necessary experience and human centered approaches to our urban and regional settings. This book describes 30 Human Factors methods for use in the LUP & UD context. While it explores theory, it also focuses on the question of what Human Factors methods are; their advantages and disadvantages; step-by-step guidance on how to carry them out; and case studies to guide the reader.
Keywords: Stadtplanung; Raumplanung; Flächennutzungsplanung; Urbanismus; Gebaute Umwelt; Mensch; Planungsinstrument